Seismological behavior in the Peru using dimension fractal - Mantilla N., Irla (2007)
The present work is a sample of application of the measure concepts and dimension of geometry fractal in the simulation of the process of fragmentation applied to the study of the seismological behavior in Perii. In this investigation it is looked for to relate the concepts of statistical distribution and fractal dimension; in the purpose of being able to express justifiably in a realler way, the behavior of magnitude frequency and latitude of seismic occurrence.